2011
DOI: 10.3851/imp1762
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,2,4-triazole and Purine Acyclic Cyclopropane Nucleoside Analogues: Synthesis, Antiviral and Cytostatic Activity Evaluations

Abstract: Evaluation of their affinity for herpes simplex type 1 (HSV-1) and varicella-zoster virus-encoded thymidine kinases (VZV TK) also showed that none of the compounds was able to significantly inhibit 1 µM deoxythymidine phosphorylation by HSV-1 and VZV TK at 500 µM concentrations. The in vitro cytostatic activity evaluation results indicated a weak antiproliferative activity for all tested compounds. Only 6-pyrrolylpurine derivative bearing a carboxylic group substituted cyclopropane ring produced a rather sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A-5021 exhibited potent activity against HSV-1, HSV-2, and VZV that was superior to the clinically acyclovir drug, as well as a potent inhibitor of Epstein-Barr virus, which was equipotent to the acyclovir. [55] Wittine et al prepared a series of molecules containing 3substituted 1,2,4-triazole moiety linked via ethylene spacer to lactone or lactam functionality to yield 1,3-disubstituted 1,2,4triazole l-ascorbic acid (29)(30)(31)(32)(33) and imino-ascorbic acid (33) derivatives ( Figure 9). Their inhibition of the hepatitis C virus replication in the Huh 5-2 replicon system was assessed.…”
Section: Ribavirinmentioning
confidence: 99%
See 1 more Smart Citation
“…A-5021 exhibited potent activity against HSV-1, HSV-2, and VZV that was superior to the clinically acyclovir drug, as well as a potent inhibitor of Epstein-Barr virus, which was equipotent to the acyclovir. [55] Wittine et al prepared a series of molecules containing 3substituted 1,2,4-triazole moiety linked via ethylene spacer to lactone or lactam functionality to yield 1,3-disubstituted 1,2,4triazole l-ascorbic acid (29)(30)(31)(32)(33) and imino-ascorbic acid (33) derivatives ( Figure 9). Their inhibition of the hepatitis C virus replication in the Huh 5-2 replicon system was assessed.…”
Section: Ribavirinmentioning
confidence: 99%
“…[105] In 2012, Muratore et al identified small molecule compounds capable of inhibiting the growth of influenza A and B viruses in cultured cells effectively and specifically by targeting a viral RNA-dependent RNA polymerase assembly interface. They have developed ELISA to measure interactions between PA and PB1 by the use of the synthesized PB1 1-15 À Tat peptide (PTP), which has a C-terminal sequence, from the HIV Tat protein (amino acids [47][48][49][50][51][52][53][54][55][56][57][58][59]. The known PAÀ PB1 interaction inhibitor was tested by increasing concentrations of synthetically PB1-derived peptide (amino acids 1-15) fused to the translocating domain of HIV Tat protein (PB1 1-15 -Tat peptide).…”
Section: Non-nucleoside Bridgehead 124-triazolesmentioning
confidence: 99%
“…Wingrove et al put forward a hypothesis that the activity of loreclezole (30) (second-generation antiepileptic drug) is dependent on the interaction between the triazole moiety and the amide group of asparagine (Asn-289), which is located on the β2 subunit of the GABAA receptor [94]. [98].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…To date, however, only very few compounds (mainly acyclic guanosine analogs) have been reported to show inhibitory activity towards VZV TK [5,6]. In contrast, a large number of antiviral agents have been successfully developed that target the TKs of other members of the herpesvirus family, especially herpes simplex virus type 1 (HSV-1).…”
Section: Introductionmentioning
confidence: 95%